Foldable desk divider - Abdul Aziz, Mohammad Azhan; Rosman, Imi Raihanah; Ahmad Tamizi, Nur Annisya; Mohamed Nazim, Fatin Humaira (Universiti Teknologi MARA, Kedah, 2019)
Many students who come to the library that need to accomplish their work or assignments need some personal workspace in order to feel comfortable and some privacy. Same goes to the office worker they will feel uncomfortable and disturbed if it is too crowded by sharing the same desk. Therefore, this project is designed to facilitate them and it is also suitable for all users too.